Delphic and Odyssean monetary policy shocks: Evidence from the euro area - Philippe Andrade; Filippo Ferroni (Federal Reserve Bank of Boston, 2019)
What drives the strong reaction of financial markets to central bank communication on the days of policy decisions? We highlight the role of two factors that we identify from highfrequency monetary surprises: news on future macroeconomic conditions (Delphic shocks) and news on future monetary policy shocks (Odyssean shocks). These two shocks move the yield curve in the same direction but have opposite effects on financial conditions and macroeconomic expectations. A drop in future interest rates that is associated with a negative Delphic (Odyssean) shock is perceived as being contractionary (expansionary). These offsetting effects can explain why central bank communication leads to a strong reaction of the yield curve together with a weak reaction by inflation expectations or stock prices. The two shocks also have different impacts on macroeconomic outcomes, such that central bankers cannot infer the degree of stimulus they provide by looking at the mere reaction of the yield curve. However, changes in their communication policy can influence the way markets predominantly understand communication about future interest rates.
Keywords: E52; E32; C10; 330; central bank communication; yield curve; monetary policysurprises; signaling; forward guidance